Culturological direction in Kazakh language and lingvocultural units in Chinese translation of Abay’s works. (Journal of Oriental Studies, 2016)
This article provides a methodological framework, describes recent research directions lingvoculture in Kazakhstan and Culturological direction in Kazakh language and lingvocultural units in Chinese translation of Abay’s works.